Selected literary criticism - James, Henry (McGraw-Hill Book Company, 1965)
In this collection of essays James gives us his thoughts on Whitman, Taine, Swinburn, Emerson, Guy de Maupassant, Zola, and other authors coming from The Nation, The Atlantic Monthly, Fortnightly Review and other magaizines in the years 1865 through 1914. As the editor says, "The reader of some of those [Literary Reviews and Essays by Henry James] might well agree with James' contemporaries that the young James is much more strikingly intelligent, unconventional and right as a critic than as a writer of fiction.